Measuring the application of total quality management in Karkh Maternity Hospital from the perspective of health staff - عطشان فوزي هاشم; كاظم ايمان عبد الغني (Journal of Economics and Administrative Sciences, 2019)
Quality is the key to success in today’s world, which is based mainly on competition in the provision of high quality services through the application of the modern management method which is called total quality management in organizations. This includes describing the provision of health services and satisfaction of patients . . Aim : the aim of this study was to Measuring the application of total quality management in Karkh maternity Hospital from the opinions of paramedical staff to the importance of the total quality management in Alkarkh maternity hospital in the Baghdad Karkh health directorate because its specialized hospital for maternity and get the title or (nickname) of the hospital friend of the child . Methodology : based on the descriptive and analytical methods , in order to test the hypothesis of this study we used test of stability (Cronbach Alpha) and test of (Kolmogorov-Smirnov) , frequencies and percentages through the statistical package program of social sciences SPSS V.16 to analyze the data which collected by relying on a questionnaire which is distributed to paramedical staff at Karkh maternity Hospital , The sample size included all paramedical staff in the hospital included were (100) individuals the percentage of response was (91%) ,during the period May ,June and July 2018 Results: - The search showed that the health staff in Karkh maternity hospital are perceive and understood the concept of importance of the of total quality management , with high degree of perception to all three parts (principles, advantages and obstacles) for total quality management - The sequence of the three axis principles according to the level of perception of the research sample from the top to the lowest (the axis principles first and then the axis of the advantage and finally the axis of obstacles to the application of total quality management - The search showed a relationship between the demographic variables of the study sample (age, gender, job title and years of experience) and the perception of the health staff at Karkh maternity hospital for the concept of the importance of application of total quality management